Modeling fabrication, and measurement of laterally-coupled distributed feedback lasers - Millett, Ronald R (University of Ottawa (Canada), 2009)
This thesis describes the modeling, design, fabrication, experiment, and measurement analysis of a 1310 nm laterally-coupled distributed feedback (LC-DFB) laser diode with higher order gratings. In LC-DFB lasers, a grating is etched directly out of the waveguide ridge, eliminating regrowth steps. We propose the use of stepper lithography for LC-DFB laser fabrication, a technique more suitable for high-volume manufacture than traditional approaches, such as electron-beam lithography. We also propose the use of higher order gratings, requiring larger grating periods than first-order gratings, to improve manufacturing tolerances. Simulations using Streifer's modified coupled-mode approach were used to explore the laser design space. This thesis extends the original formulation to a two-dimensional cross-section to accurately model the LC-DFB lasers. The effective coupling coefficient, Keff, calculated using this approach varied considerably from the generally used simple coupling coefficient, Kp, found when neglecting Streifer correction terms. Our model determined that larger duty cycles (> 0.5), and greater ridge width contrasts produce higher |Keff| values. The inclusion of a gamma/4 phase-shift tends to degrade higher order grating performance. Non-rectangular grating shapes, such as triangular and sinusoidal, often have stronger coupling, particularly at higher grating orders, and are potentially simpler to fabricate. The fabricated lasers had excellent side-mode suppression ratios of > 50 dB. The efficiencies and threshold currents of the LC-DFB lasers are comparable to the Fabry-Perot lasers, indicating that the higher order grating losses are not prohibitive. The single-mode yield was compromised by weaker than expected gratings due to rounding during fabrication, and cross-wafer variations, however, yields of ∼50% on the best design variations are very promising, particularly for a first fabrication mn. The overall performance indicates that with some design improvements, guided by our model, this laser has commercial potential. The experimentally determined Keff matched well with the simulated values, within fabrication and experimental variations.
Keywords: Engineering, Electronics and Electrical.